2018
DOI: 10.3389/fpls.2018.00229
|View full text |Cite
|
Sign up to set email alerts
|

QTL-By-Environment Interaction in the Response of Maize Root and Shoot Traits to Different Water Regimes

Abstract: Drought is a major abiotic stress factor limiting maize production, and elucidating the genetic control of root system architecture and plasticity to water-deficit stress is a crucial problem to improve drought adaptability. In this study, 13 root and shoot traits and genetic plasticity were evaluated in a recombinant inbred line (RIL) population under well-watered (WW) and water stress (WS) conditions. Significant phenotypic variation was observed for all observed traits both under WW and WS conditions. Most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 42 publications
2
34
0
Order By: Relevance
“…Construction of an appropriate mapping population is a prerequisite for QTL analysis. In this study, a maize RIL population derived from two Chinese maize elite inbred lines, DH4866 and T877 with high recombination frequency [19] was employed to identify the genetic loci conferring resistance to GER.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Construction of an appropriate mapping population is a prerequisite for QTL analysis. In this study, a maize RIL population derived from two Chinese maize elite inbred lines, DH4866 and T877 with high recombination frequency [19] was employed to identify the genetic loci conferring resistance to GER.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic linkage map contained 1,868 bin markers and spanned a total length of 3,081.8 cM, with a mean interval length of 1.65 cM. Detailed information on construction of the bin map has been reported previously [19].…”
Section: Plant Materials and Genotypingmentioning
confidence: 99%
“…CR number significantly varied among maize genotypes in a quantitative manner ( Burton et al, 2014 ) and it has been suggested that low CR numbers improve resource acquisition under drought ( Gao and Lynch, 2016 ). On the other hand, a recent study found non-significant genotype × environment (G × E) interaction between CR number and different water regimes in a recombinant inbred line (RIL) population of maize ( Li et al, 2018 ). Several QTLs associated with CR angle and CR length were identified instead as having antagonistic pleiotropic effects in response to water deficiency, a result that might be linked to the partially overlapping function of RCTS and RCTL ( Li et al, 2018 ).…”
Section: Role Of Shoot-borne Root Architecture In Nutrient Capture Anmentioning
confidence: 97%
“…On the other hand, a recent study found non-significant genotype × environment (G × E) interaction between CR number and different water regimes in a recombinant inbred line (RIL) population of maize ( Li et al, 2018 ). Several QTLs associated with CR angle and CR length were identified instead as having antagonistic pleiotropic effects in response to water deficiency, a result that might be linked to the partially overlapping function of RCTS and RCTL ( Li et al, 2018 ). Conversely, maize genotypes with large CR number have shallower rooting depth and improved phosphate acquisition from low-phosphate soils ( Sun et al, 2018 ).…”
Section: Role Of Shoot-borne Root Architecture In Nutrient Capture Anmentioning
confidence: 97%
“…Quantitative trait locus (QTL) analysis provides an effective means of dissecting the genetic basis of complex trait in plants and animals (Zeng 1994;Alonso-Blanco et al 2009). Marker-assisted selection (MAS) based on QTLs can greatly facilitate crop improvement (Prasanna et al 2010;Li et al 2018).…”
Section: Introductionmentioning
confidence: 99%